Tingkat Kecemasan Dental Pada Anak Usia 5-8 Tahun Saat Kunjungan Pertama ke Dokter Gigi di RSGM Universitas Kristen Maranatha - Sinta Ramah Sari; Lisa Imelia; Linda Sari Sembiring (SONDE (Sound of Dentistry), 2023)
Children's anxiety about dental treatment causes impacts such as longer treatment time, and rejection of dental care. Anxiety about dental treatment causes patients reluctant to seek treatment for dental health care units. The first time a child is anxious about dental treatment because of ignorance. Anxiety that is common in children is a sense of not knowing and worry about dental examinations. The purpose of this study was to determine the level of anxiety in children when they first visited the dentist at Maranatha dental hospital. Type of research is descriptive with cross sectional design using accidental sampling technique. The study was conducted using the pulse with fingertip pulse oxymeter, Corah Dental Anxiety Scale (CDAS) questionnaire, and observation of anxiety. The subjects used 50 children aged 5-8 years. The results based on the pulse rate it is known that the subject has a normal pulse rate of 56.0%, based on the CDAS method are known the subjects have high anxiety by 54.0%, and based on observations is known the subjects have a high anxiety of 62.0%. Conclusions of this study, if viewed according to based on pulse measurement using digital fingertip pulse oxymeter showed normal anxiety, the method of CDAS as high anxiety, then the anxiety observation methods show the results of high anxiety.